2002
DOI: 10.1038/nsb752
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic partitioning of protein folding and aggregation

Abstract: We have systematically studied the effects of 40 single point mutations on the conversion of the denatured form of the alpha/beta protein acylphosphatase (AcP) into insoluble aggregates. All the mutations that significantly perturb the rate of aggregation are located in two regions of the protein sequence, residues 16-31 and 87-98, each of which has a relatively high hydrophobicity and propensity to form beta-sheet structure. The measured changes in aggregation rate upon mutation correlate with changes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
419
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 399 publications
(449 citation statements)
references
References 47 publications
28
419
0
2
Order By: Relevance
“…Formation of non-native extended ␤-sheet conformation appears to promote aggregation, and induction of non-native helix conformation correlates with the inhibition of protein aggregation. Similar observations were made by Dobson and co-workers, based on exhaustive point mutations in the muscle acylphosphatase protein (35,36). A clear-cut kinetic partitioning between aggregation and folding of proteins was observed.…”
Section: Resultssupporting
confidence: 72%
“…Formation of non-native extended ␤-sheet conformation appears to promote aggregation, and induction of non-native helix conformation correlates with the inhibition of protein aggregation. Similar observations were made by Dobson and co-workers, based on exhaustive point mutations in the muscle acylphosphatase protein (35,36). A clear-cut kinetic partitioning between aggregation and folding of proteins was observed.…”
Section: Resultssupporting
confidence: 72%
“…Interestingly, the experimentally determined secondary structure of apoA-I IOWA fits well with secondary structure predictive analysis of the N-terminal primary sequence (28) (Figure 5). This comparison implies that the G26R mutation allows the protein to adopt a regional structure, which is more probable based on the amino acid sequence, as found in other systems (29).…”
Section: Resultsmentioning
confidence: 90%
“…46 We expect that the increased propensity for α-helix formation compared to propensity for β-sheet should diminish the amyloidogenicity of the protein. 40 …”
Section: Charge States and Shifts In Population In Aggregation-prone mentioning
confidence: 99%
“…[30][31][32] The multitude of the amyloid-like conformers, which contain mainly β-sheets, suggested that formation of amyloid fibrils is a general property of any polypeptide chain,38 while the sequence of the protein and the environmental conditions control the rate of aggregation.38 Increased hydrophobicity, through single point mutation, of the residues not involved in the folding core of the acylphosphatase (AcP) protein was shown to increase the rate of the aggregation process. 40 The hydrophobicity of the side-chains of the quadrupole mutated S6 protein was proven to be responsible for the protein aggregation in a tetramer, with the Aβ homologous fragment forming inter-peptide antiparallel β-sheets. 41 In contrast, a decrease of the hydrophobicity in the Aβ 1-42 -protein using random screening mutations, proved to make the protein less prone to aggregate.…”
Section: Charge States and Shifts In Population In Aggregation-prone mentioning
confidence: 99%